The Manifestation Of Ethnic Solidarity In A Multiethnic Social Environment (Certain Select Region Case Study) - Sergeevna Kuzmenko, Irina (2019)
The purpose of the study is to clarify the nature of ethnic solidarity in a multiethnic social environment.  Reasons for this are both the insufficient level of theoretical status of the problem of ethnic solidarity, and the high intensity of the manifestation of intergroup conflicts based on ethnic differences and actualization of ethnosocial characteristics of the conflict subjects, which implies destructive manifestation of group solidarity. The methodological base of the study includes typological comparison, analysis, synthesis, classical methodology of sociological research, and also a modeling method. The results of the study determine the relationship between the specifics of the external distinctness of ethnic groups and the level of conflict in the interethnic environment, as well as determine the role of ethnic solidarity in the escalating of social conflicts to the level of intergroup contradictions. This study considers the process of solidarity in the context of interethnic relations. In particular, the study derives the notion of ethnic solidarity. A particular example of a multiethnic region is the Krasnodar Territory, where one of the authors of the publication (V. Plotnikov) conducted a cycle of external studies of interethnic relations. Particular conclusions drawn from the examination and analysis of manifestations of ethnic solidarity in the multiethnic social environment of a particular region are the basis for similar review of the situation in other regions and are universal. The paper studies the negative forms of the manifestation of ethnic solidarity, the attendant factors, and also gives a local example of consideration of the factors of negative ethnic solidarity. At the end of the study, the authors outline methodological recommendations on the settlement and resolution of the problem of negative ethnic solidarity in the multiethnic region, with the possibility to apply them in the course of regulating social processes in the interethnic environment.